Agrópolis: Célula Simbiótica Productiva (2021)
This document investigates the different variables in the research on the development of a city growth model in its border areas, the development of this research focuses on the city of Medellín, in the department of Antioquia, where it is chosen a border area in which the greatest environmental and social impact can be developed, since in these areas there are phenomena of displacement, invasion of the city's green belts and food insecurity. To guarantee an integral solution to all these variables, it is proposed to develop a peri-urban piece that serves as a mitigation and transition cushion between the dynamics of the city and sub-urban areas such as the green belt of Medellín, to guarantee these transitions. environmental issues such as the incorporation of solutions for displaced people and food insecurity, this peri-urban piece is endowed with a sustainable agricultural production system, which incorporates productivity, processing and demand with the aim of bypassing all intermediaries in the chain traditional production, which make food products more expensive and affect through inflation, putting food security at risk in Medellín.